Earthquake vulnerability mapping based on probabilistic seismic hazard analysis (PSHA) in the Nias Islands, Indonesia - Astri Angraeni; Lailatul Husna Lubis; Ratni Sirait; Reinhard Sipayung (Universitas Riau, 2024)
The Nias Islands are categorised as seismically active, making them susceptible to earthquakes. The Nias Islands region is situated on the ring of fire and a subduction line that experiences annual movement, which is the primary factor contributing to its susceptibility to earthquakes. The occurrence of earthquakes in the Nias Islands is supported by a documented record of 7,152 incidents with a magnitude strength more than 4 Mw from 1910 to 2022, indicating a 500-year return period. In order to assess the susceptibility of the Nias Islands region to earthquakes, a process called earthquake vulnerability mapping is conducted. This involves utilising the probabilistic seismic hazard analysis (PSHA) approach to calculate the peak ground acceleration value. The investigation commences with gathering seismic events within the study region from the IRIS and BMKG catalogues. The earthquake data was subsequently transformed from magnitude to Mw (magnitude moment), and then de-clustered to isolate the primary event from the entire dataset of earthquakes. First, the a-value and b-value are calculated in order to identify the background earthquake source. Then, PSHA processing is conducted to calculate the spectral acceleration value for each predefined grid. The processing findings indicate that the peak ground acceleration (PGA) value at time 0 s ranges from 0.05 – 1.2 g, the PGA value at time 0.2 s ranges from 1 – 1.2 g, and the PGA value at time 1 s ranges from 0.4 – 0.5 g.